Long-term outcome of vagus nerve stimulation therapy in drug-resistant epilepsy: a retrospective single-center study - Si Chen; Xiaxin Yang; Shujun Xu; Baomin Li; Chao Li; Ning Yang; Xue Yang; Xiaotang Wang; Shuo Xu; Xiuhe Zhao; Xiuhe Zhao (Frontiers in Neurology)
IntroductionVagus nerve stimulation (VNS) has garnered widespread application in patients with drug-resistant epilepsy (DRE), while the efficacy and prognostic factors of VNS in DRE remain elusive. Moreover, clinical determinants associated with rapid response to VNS have never been uncovered. This study aimed to elucidate factors influencing efficacy and rapid response to VNS.MethodsA consecutive series of patients with DRE undergoing VNS surgery from January 2014 to December 2023 was collected to describe VNS efficacy. Both univariate and multivariate analyses were performed to identify statistically significant prognostic factors, and a predictive model was developed. Furthermore, we examined clinical determinants of rapid/slow response to VNS and VNS current changes.ResultsA total of 65 patients underwent VNS implantation. Seizure frequency significantly decreased post-VNS, with mean seizure reduction rates of 35.7, 49.0, 48.5, 52.8, 63.2, and 66.8% at 6 (n = 65), 12 (n = 65), 24 (n = 50), 36 (n = 40), 60 (n = 31), and 84 (n = 19) months, respectively. At final follow-up, 61.5% (40/65) were responders (50–100% seizure reduction), and 10.8% (7/65) achieved seizure freedom for ≥1 year. Univariate analysis identified age at seizure onset ≥6 years (p = 0.003), baseline seizure frequency ≤30/month (p = 0.001), focal seizures (p = 0.002), developmental and epileptic encephalopathies (p = 0.037), and surgical history (p < 0.001) as significant prognostic factors. Multivariate analysis confirmed age at seizure onset ≥6 years (OR: 5.726, p = 0.039), baseline seizure frequency ≤30/month (OR: 4.697, p = 0.048), and focal seizures (OR: 4.791, p = 0.025) as independent predictors, enabling the development of a predictive model for VNS efficacy. Additionally, among responders, the median response duration was 6 months (range: 1–60 months), with baseline seizure frequency ≤30/month significantly associated with rapid response of VNS in DRE (<6 months, p = 0.033).ConclusionVagus nerve stimulation is effective for treating DRE, with efficacy increasing with follow-up duration. Age at seizure onset ≥6 years, baseline seizure frequency ≤30/month, and focal seizure were predictive of VNS success, underscoring the need for careful preoperative assessment of patients with DRE before VNS surgery.